الإمامة في الفكر الاستشراقي -قراءة تحليلية نقدية في موجز دائرة المعارف الإسلامية - الشرع, أحمد (University of Eloued جامعة الجزائر, 2020)
"تناولت في هذه الدراسة مسألة الإمامة في الفكر الاستشراقي، وذلك من خلال موسوعة موجز دائرة المعارف الإسلامية، وإشكالية الدراسة المرجو الإجابة عنها تتمثل في التساؤل عن نظرة المستشرقين في مسألة الإمامة من خلال الموجز و أثرها في الفكر والدراسات الاسلامية. وقد قسم موضوع الدراسة إلى مقدمة وثلاثة مباحث بينت فيها موقف المستشرقين من المسألة بالإضافة إلى الخاتمة التي جمعت فيها نتائج الدراسة، وكانت أهم النتائج المتوصل إليها بُعد المستشرقين عن الأمانة العلمية في كتابام عن مسألة الإمامة، وأنه كانت لذلك الموقف المغرض في موجز الدائرة وغيرها من الدراسات كذلك أثر واضح في تبني من كتب من المسلمين في هذا الموضوع""In this study I have dealt with the matter of IMAMA(leading) in Orientalist thought, and this is throught the Encyclopedia summary of the Islamic knowledge ,and the reason of this study that we will hope to answer is the question about the Orientalists 'view of the IMAMA through the summary and its effect on the Islamic studies and thought. the subject of our study is divided into an introduction and three chapters which I focused in ,the opinion of the Orientalists fron this matter in addition to that the conclusion which I collected in all the effects of the study. And it was the most important effects after the Orientalists for the scientific honesty in their writings about this subject. and it was for the opposite view in the circle of the summary and other studies also had a clear effect on the adoption of Muslim books on this topic."
مذكرة ماستر تخصص عقيدة
Keywords: "الإمامة -الفكر - الاستشراق- قراءة - نقدية - موجز - المعارف الإسلامية "; The Imamate - Thought - Orientalism - Reading - Critical - Brief - Islamic knowledge